Program Konseling Karir Di MAN 1 Medan - Dira Nadira Amelia Siahaan; Mega Iswari; Afdal Afdal (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
Careers are the "new world" that individuals will face after studying, professionalism and education. Indeed, a career becomes a vehicle for individuals to develop themselves both aspects of knowledge, attitudes and skills. For students, career counseling becomes important as a provision to face the world of work. This paper reviews the career counseling program at MAN 1 Medan. The formulation of this study is focused on how the orientation, implementation, and indicators of the success of career counseling programs at MAN 1 Medan. To obtain data, in-depth interview techniques, participant observation and documentation study were carried out. Furthermore, the data were analyzed using data reduction, data presentation, and conclusion drawing techniques. Finally, the validity of the data is obtained through triangulation techniques (both sources and methods) and perseverance of observation. The results of this study indicate that (1) orientation of career counseling is aimed at attention to the needs and problems of students in developing the careers of students, (2) the implementation of career counseling MAN 1 Medan is given according to student needs, by involving various parties in communicating and coordinating to help students in increasing their students 'potential, and (3) the success of MAN 1 Medan's career counseling program, one of which is shown by the students' interest to go to college quite enthusiastically, even so many students are accepted in various public and private universities, both in Sumatra , Java, also abroad.